A Model of the Information World of Serious Recreational Athletes - Adams, Suellen S. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This poster shows a model of information behavior among serious recreational athletes and examines the possible implications for other groups. The three-level model was derived in a primarily qualitative study of amateur duathletes, triathletes, runners, cyclists and swimmers who had trained for and completed at least one event. Cette affiche illustre un modèle de comportement informationnel chez les athlètes récréosportifs et examine l’implication possible d’autres groupes. Le modèle de trois phases est dérivé d’une étude principalement qualitative auprès de duathlètes, de triathlètes, de coureurs, de cyclistes et de nageurs amateurs qui ont participé à au moins un événement.